The Effectiveness of Law Enforcement Volunteers in Prosecuting Sharia Violations: A Study of the Role of Muḥtasib and Pageu Gampong in Banda Aceh - Mizaj Iskandar Usman; Abdul Jalil Salam; Muliadi Muliadi; Nurdin MH; Amrizal J. Prang (Fakultas Syariah UIN Sultan Aji Muhamamd Idris Samarinda, 2026)
This study aims to explain the roles of the muḥtasib and pageu gampong in enforcing sharia law in Banda Aceh, as well as their respective effectiveness. The study is important because the extensive area covered by sharia law enforcement creates gaps in supervision and enforcement that formal authorities have not yet fully addressed. The research questions focus on the similarities and differences in the authority of these two institutions, and the factors that influence their effectiveness. The study employs a qualitative legal-sociological approach by analyzing institutional practices at the gampong level. The results suggest that muḥtasib and pageu gampong have similar roles involving monitoring, admonishing, and reporting violations of sharia law. However, muḥtasib is limited to these three functions, whereas the pageu gampong also has the authority to resolve customary disputes, particularly minor criminal and civil cases. Pageu gampong is more effective in terms of performance because it stems from the community's collective consciousness, is self-reliant and voluntary, and has a broader membership. Nevertheless, it is not yet widespread, with only twelve villages in Banda Aceh currently having an active pageu gampong.